Instant-Messagers Really Are About Six Degrees from Kevin Bacon; Big Microsoft Study Supports Small World Theory - Horvitz, Eric (The Washington Post - Washington, D.C., 2008)
Turns out, it is a small world. The "small world theory," embodied in the old saw that there are just "six degrees of separation" between any two strangers on Earth, has been largely corroborated by a massive study of electronic communication.